Risk factors and heat reduction intervention among outdoor workers: a narrative review - Lim, Mei Ching; Khamisah Awang Lukman; Nelbon Giloi; Mohammad Saffree Jeffree; Saihpudin @Sahipudin Saupin; Pravina Deligannu (Universiti Putra Malaysia, 2023)
With the ongoing climate change, heat waves are anticipated to become more frequent and intense. Hence, heat-reduction interventions are essential, particularly for outdoor workers. Although numerous studies focused on heat stress among outdoor workers, there is little evidence of a comprehensive heat prevention program. This review relied on secondary sources from various sources and databases, including ProQuest(361), Springerlink(398), ScienceDirect(698), and Google Scholar (54). This review aims to identify the risk factors of heat stress and appraise the various heat reduction strategies. The risk factors identified include environmental elements, occupational factors, and individual characteristics. As no one method suits all occupations, a holistic heat prevention program that incorporates effective interventions is crucial. This includes an adequate water-rest cycle, heat-related awareness training, and individualised cooling techniques (bandanna, cooling vest or uniform). This acceptable, affordable, accessible, and sustainable program will improve the workers’ comfort while lowering the incidence of heat-related illnesses and mortality.